Co-effects of calcium carbonate and sodium bisulfite modification on improving water resistance of soy protein adhesives - Tong, Tianjian (Kansas State University, 2012)
Bio-based protein adhesives derived from renewable resources, especially soy protein are becoming more significant due to the concerns about environment and health related issues and the limit of petroleum recourses. However, the relatively poor water resistance of soy-based protein adhesives limits its wide applications. The goal of this study was to improve the water resistance performance of soy-based protein adhesives by chemical modification. The specific objectives are 1) to modify soy protein with calcium carbonate (CaCO[subscript]3) and sodium bisulfite (NaHSO[subscript]3) as the denaturing agents; 2) to investigate the effects of calcium carbonate (CaCO[subscript]3) concentrations, curing time and curing temperatures on adhesion performance of the modified soy-based protein adhesives. In this study, the co-effects of NaHSO[subscript]3 and CaCO[subscript]3 on adhesion properties of soy protein adhesives were investigated. NaHSO[subscript]3 was added to soy flour slurry at constant concentration 6g/L, while concentration of CaCO[subscript]3 was chosen in the range of 0 to 23g/L. Soy protein adhesives modified with 4g/L and 16g/L CaCO[subscript]3 were selected to characterize the adhesion performance on 3 ply yellow pine plywood using the Response Surface Method (RSM). The effects of curing temperature and curing time on the adhesion properties were also studied. The major findings are 1) 4g/L CaCO[subscript]3, 6g/L NaHSO[subscript]3 modified soy protein adhesives (MSPA) had better adhesion performance (both dry and wet) than 16g/L CaCO[subscript]3, 6g/L NaHSO[subscript]3 MSPA; 2) Higher temperature (170°C) resulted in higher wet shear adhesion strengths; 3) Longer hot press time had positive impact on wet adhesion shear strength; and 4) 4g/L CaCO[subscript]3, 6g/L NaHSO[subscript]3 MSPA showed better adhesion shear strength after 2 weeks storage than 16g/L CaCO[subscript]3, 6g/L NaHSO[subscript]3 MSPA. In general, 4g/L CaCO[subscript]3, 6g/L NaHSO[subscript]3 MSPA, under longer hot press time and higher temperature would lead to a better adhesion performance.
Keywords: Soy protein adhesive; Calcium carbonate; Water resistance; Biology (0306)